2012
DOI: 10.1186/1471-244x-12-123
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of co-morbid depression in out-patients with type 2 diabetes mellitus in Bangladesh

Abstract: BackgroundLittle is known about the prevalence of depression in people with diabetes in Bangladesh. This study examined the prevalence and factors associated with depression in out-patients with Type 2 diabetes in Bangladesh.MethodsIn this cross-sectional study a random sample of 483 diabetes out-patients from three diabetes clinics in Bangladesh was invited to participate. Of them 417 patients took part. Depressive symptoms were measured using previously developed and culturally standardized Bengali and Sylhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
86
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 37 publications
13
86
3
2
Order By: Relevance
“…Further, depression was strongly associated with poor glycemic control and number of co-morbid conditions. 46 In our study also we found that, depressive symptoms are related with age, duration, and glycemic control of diabetes.…”
Section: Discussionsupporting
confidence: 69%
“…Further, depression was strongly associated with poor glycemic control and number of co-morbid conditions. 46 In our study also we found that, depressive symptoms are related with age, duration, and glycemic control of diabetes.…”
Section: Discussionsupporting
confidence: 69%
“…Using the commonly used criterion of a WHO-5 score lower than 52, suggesting poor emotional well-being,39,40 29.4% of older adults compared with 34.7% of young people reported poor emotional well-being (χ 2 =8.46; P <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…PHQ-9 consists of 9 items and the total score varies between 0 and 27 [29]. Standard PHQ-9 cut-off scores were used to classify minimal (0-4), mild (5-9) and moderate to severe (≥ 10) symptoms of depression [30]. In this study, positive for depressive symptoms was defined as PHQ-9 scores > 5 to identify mild mental health problems, because it is not common that active working medical doctors have a severe mental health problem.…”
Section: Discussionmentioning
confidence: 99%